Prevalence and correlates of depression and psychological distress among garment factory employees in Hambantota district, Sri Lanka - Lasith Obadaarachchi; Amila Isuru; Suwin Hewage; Manuja Vipuladasa; Shehan S.Williams (BMC Psychology)
Abstract Background Garment factory employees have been identified as a high-risk population for developing depression in Asian countries. Depression is recognised as a potentially reversible risk factor for low productivity in the garment factory workforce. Therefore, identification and treatment of depression in garment factory workers can improve productivity and their quality of life in general. The study aimed to determine the prevalence and correlates of depression in garment factory workers in the Hambantota district, Sri Lanka. Methods This is a cross-sectional descriptive study. The calculated sample size was 381, and a multistage random sampling method was used. Culturally validated General Health Questionnaire-12 and Beck Depression Inventory–II were used to screen for psychological morbidity and depression, respectively. Results The majority of 381 employees were females (n = 325, 83.3%). The mean age was 32.9 years (SD—10.45 years). The prevalence of depression in the study sample was 16.80% (95% CI: 13.04–20.55%). Depression was associated with the presence of a chronic medical condition (OR-3.51, 95% CI:1.61–7.67), family history of psychiatric illness (OR-3.03 95% CI-1.11 to 8.26), history of deliberate self-harm (OR-10.79 95% CI-4.68 to 24.89), history of psychiatric illness (OR-6.12, 95% CI-2.39-15.73), and being divorced or separated from their partner. The only job-related factor that correlates with depression was working extra duty hours (OR-1.74, CI 1.01–3.02). Conclusions The prevalence of depression among garment factory employees in Hambantota district is higher than the national average. However, it is relatively lower compared to garment factory populations in other developing Asian countries.